A cost-analysis study to estimate the expenditure incurred by heroin-dependent patients before and after availing treatment for substance use disorder at an apex drug de-addiction center - S. Sivaraman; Rajesh Harsvardhan; Atul Ambekar; Rakesh Lal; Anusha Shukla; Saima Alvi (Wolters Kluwer -Medknow Publications, 2023)
Introduction: Cost-analysis can help hospital administrators and policy-makers to determine how well their institution meets this public need. As financial management technique, cost-analysis helps to furnish the necessary data for making more informed decision on operations and infrastructure investments. Keeping this in mind, a study to estimate the cost spent by heroin-dependent patients before and after availing treatment for substance use disorder in a defined study population was conducted in National Drug Dependence Treatment Center (NDDTC), Ghaziabad. Methodology: A descriptive observational study conducted in outpatient department (OPD) of NDDTC on Male, heroin-dependent patients seeking treatment from NDDTC OPD, Ghaziabad. Results: The median of total expenditure incurred by patients on substance use (considering procurement of substance, transport, and lost productivity) before coming to treatment was Rs. 527/day. The median of total expenditure incurred by patients after initiating treatment at NDDTC (considering continued substance, transport to NDDTC, lost productivity, and purchasing medicines from outside) was Rs. 34/day. Thus, amount saved by the patients after starting treatment was Rs. 492.62/day. Even after considering the expenses incurred by the NDDTC in treatment, amount saved is Rs. 445.04/day. Conclusion: This study successfully demonstrated that even after adding the expenditure by the NDDTC to the expenditure by the patients on the treatment, treatment at NDDTC does result in a considerable reduction of overall costs. This is an indirect pointer towards cost-benefit of drug treatment.